Tree Profile of Littoral Portuguese Maritime Pine - Tavares,Mário (2004)
Pinus pinaster Aiton is ecologically well adjusted to the Portuguese west littoral sands. The silviculture of this species in even aged, high forest stands produce tall, large trees, showing very peculiar technological characteristics. Within maritime pine stands, selective low thinning promotes the segregation of three main representative tree hierarchic statutes - dominated, medium and dominant. These statutes, tree age and spacing, original sample site and some artificial pruning applied during youth, have some influence in the dimensional partition of tree profiles into three parts, namely crown occurrence and vitality - alive and dead crown and clear trunks. A sample of 96 trees chosen from three Portuguese west littoral forests was divided equally into those three statutes and was used to evaluate their mean sizes and to model their relationship with those factors. Main results are (a) the size of live crown increases with tree statute inside the stand, (b) for a given age, tree statute does not determine significant differences in dead crown depth, and (c) the main trunk depth tends towards the highest values in the medium trees. Furthermore, (d) live crown depth is independent of provenance and hierarchic factors, (e) the northern littoral region trees exhibit the biggest crown depths, (f) dominant trees tend to exhibit smaller main trunk depth and (g) artificial pruning must be applied as high as possible up the main trunk.